POC11 Multiple radiculopathies and cranial nerve palsies in association with chronic lymphocytic leukaemia and lupus anti-coagulant treated with rituximab. Issue 11 (22nd October 2010) - Morrow, J; Page, R; Al Hilali, M; D'Sa, S; Reilly, M M
Abstract : A 53 year old woman with a 3-year history of progressive weakness and numbness of all four limbs and multiple cranial nerve palsies is presented. She had been diagnosed with chronic lymphocytic leukaemia (CLL), Rai stage 0, 1 year into her neurological illness. Laboratory investigations showed a positive lupus anticoagulant in addition to mild lymphocytosis. Magnetic resonance imaging of the entire neuroaxis with gadolinium and cerebrospinal fluid analysis were normal. Nerve conduction studies were normal. Electromyography showed changes of chronic denervation in face and limb muscles suggestive of multiple radiculopathies. Her neurological syndrome had previously failed to respond to anticoagulation, oral fludarabine or corticosteroid treatment. The clinical diagnosis was of CLL-associated immune mediated preganglionic neuropathy. She was treated with rituximab and had a dramatic response with return to normal strength 2 months after completing treatment. The associations between CLL, neuropathy and antiphospholipid antibodies are reviewed.